2020
DOI: 10.3390/ijerph17103673
|View full text |Cite
|
Sign up to set email alerts
|

Full Radiology Report through Patient Web Portal: A Literature Review

Abstract: The aim of this study discusses the gap between the patient web portal and providing a full radiology report. A literature review was conducted to examine radiologists, physicians, and patients’ opinions and preferences of providing patients with online access radiology reports. The databases searched were Pubmed and Google Scholar and the initial search included 927 studies. After review, 47 studies were included in the study. We identified several themes, including patients’ understanding of radiology report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 72 publications
1
9
0
Order By: Relevance
“…To our knowledge, this study is the first to explore patients’ needs and gaps in radiology reports using these sources. Previous studies that have focused on patients’ opinions or challenges related to patients being able to access their full radiology report indicated that patients had an interest in having full access to these reports [ 4 , 18 ]. A study showed that 51% of patients had a strong desire to obtain their radiology reports without obstacles or challenges [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, this study is the first to explore patients’ needs and gaps in radiology reports using these sources. Previous studies that have focused on patients’ opinions or challenges related to patients being able to access their full radiology report indicated that patients had an interest in having full access to these reports [ 4 , 18 ]. A study showed that 51% of patients had a strong desire to obtain their radiology reports without obstacles or challenges [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the field of radiology, radiologists and the doctors radiologists refer patients to complain about the lack of time to write reports as well as the time they must use to explain procedures to patients [ 17 ]. Giving patients access to their radiology reports provides them with the opportunity to understand the reports prior to meeting with the doctor [ 4 , 18 ]. Patients access to clear and full radiology reports enables them to share it with other specialists to obtain further explanations, second opinion, or continuous treatments [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As radiologists, we adapt to patient expectations of being able to engage directly with us to discuss their procedures and findings; the era of radiologists being “the doctors’ doctor”, remote from direct patient contact, is consigned to the past. Our work practices are adapted to increasing direct patient engagement, whether face to face or through our digital reports, which may be enhanced by tools to improve lay communication via patient portals [ 24 , 25 ]; meeting this growing expectation will enhance the lives of both patients and radiologists, and add significant value to the services we deliver [ 8 10 , 15 , 18 ].…”
Section: The Radiologist As Communicatormentioning
confidence: 99%
“…Patients are becoming the end-readers of the radiology reports with their referring physicians [ 1 , 2 ]. Patient access to radiology tests empowers the patient and allows the patient to be more informed and engaged in his or her healthcare [ 3 , 4 , 5 ]. The benefits of patient portals that allow patients to access their medical information, including radiology tests and results, have been well studied [ 3 , 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%